Better Prognosis After Complete Revascularization Using Contemporary Coronary Stents in Patients With Chronic Kidney Disease. (August 2019) - Hwang, Doyeon; Kang, Jeehoon; Yang, Han-Mo; Yang, Seokhun; Park, Jiesuck; Han, Jung-Kyu; Kang, Hyun-Jae; Koo, Bon-Kwon; Kim, Hyo-Soo
Abstract : Background: The prognostic value of angiographic complete revascularization in patients with chronic kidney disease (CKD) has not been thoroughly investigated, especially for contemporary coronary stents. We compared the clinical outcomes of complete and incomplete revascularization with second-generation drug-eluting stent, according to the presence of CKD. Methods: From the Grand Drug-Eluting Stent Registry (N=17 286) in Korea, we selected 8471 patients, who were treated with second-generation drug-eluting stent and had glomerular filtration rate and quantitative coronary angiography data (3014 [35.6%] patients with CKD and 5457 (64.4%) patients with preserved renal function). Angiographic complete revascularization was defined as a residual SYNTAX score (Synergy Between Percutaneous Coronary Intervention With Taxus and Cardiac Surgery) of 0. The primary outcome was the patient-oriented composite outcome at 3 years, including all-cause death, any myocardial infarction, and any revascularization. Results: The patient-oriented composite outcome rate after complete revascularization was significantly lower than that after incomplete revascularization in patients with CKD (14.6% versus 21.8%; adjusted hazard ratio, 0.79; 95% CI, 0.64–0.96; P =0.020) and in patients with preserved renal function (8.0% versus 12.0%; adjusted hazard ratio 0.77; 95% CI, 0.63–0.94; P =0.011). The cutoff values of residual SYNTAX scores for predicting better patient-oriented composite outcomes were different according to the presence of CKD, that is, <3 and <8 in patients with CKD and with preserved renal function, respectively. Conclusions: Angiographic complete revascularization led to better clinical outcomes in patients with CKD and with preserved renal function. However, the residual SYNTAX score to achieve a better outcome was lower in patients with CKD than with preserved renal function, favoring more aggressive revascularization in patients with CKD. Abstract : Supplemental Digital Content is available in the text.